Relationship between serum ferritin and zinc levels in patients with major thalassemia - Hervita Yeni; Finny Fitry Yani; Amirah Zatil Izzah; Gustina Lubis (Paediatrica Indonesiana, 2019)
Background In thalassemia patients, reduced zinc absorption results from increased serum iron due to repeated blood transfusions, increased iron absorption due to ineffective erythropoiesis, and competitive inhibition between iron and zinc in binding to transferrin, a means of transporting both types of minerals in the blood. Few studies have been done to examine zinc levels in thalassemia patients and its relationship with ferritin. Objective To compare serum zinc in thalassemia patients and healthy controls and to assess for a possible correlation between serum ferritin and zinc in thalassemia patients. Methods This cross-sectional study in 68 subjects was done from October 2016 to August 2017. Serum ferritin measured by chemiluminescence immunoassay and serum zinc by inductively coupled plasma mass spectrometry (ICP-MS). Wilcoxon test was used to analyze for differences between serum zinc in thalassemia patients and controls. Spearman’s correlation test was used to analyze for a possible correlation between ferritin and serum zinc in thalassemia patients. Results There were 34 patients with thalassemia and 34 healthy control subjects. The median serum zinc was 119.34 µg/dL (IQR=71.27) in the thalassemia group and 120.08 µg/dL (IQR=26.28) in the control group (P=0.36). There was no significant correlation between serum ferritin and zinc in thalassemic children (r=-0.023; P=0.895). Conclusion There is no significant difference in serum zinc levels between thalassemic children and healthy controls. There is no significant correlation between serum ferritin and zinc in thalassemic children.